Market Potential Analysis of Indonesian Cinnamon Exports in International Markets - Hasanah, Nur; Darsono, Darsono; Marwanti, Sri (Indonesian Journal of Business Analytics, 2024)
Indonesia is known as one of the world's spice-producing countries. One of the spices produced by Indonesia is cinnamon, which has many benefits and a high economic price. However, the existence of various obstacles in exporting cinnamon makes Indonesia have to select cinnamon export markets in destination countries. The purpose of this study is to analyze the potential development of Indonesia's cinnamon export markets. This research uses the analysis methods of Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and X-model potential export product. The results of the study can be concluded that the destination countries of China and India are in the position of optimistic market. While the Netherlands and Thailand are in the position of potential market.